Development of new selective synthetic methods en route to privileged scaffolds of pharmaceutical relevance - Santos, Thiago dos (2022)
Since the pioneering works of Gilman and Bebb, and Wittig and Furhmann accompanied by important contributions including Snieckus, directed ortho-metalation reactions (DoM) have found great application in the functionalization of diverse systems. Particularly, the 2,2,6,6-tetramethylpiperidyl bases by Knochel and co-workers show excellent solubility in THF, functional group tolerance, and great stability at room and higher temperatures. The cyano group is of great interest in DoMs followed by fluoro as highlighted by the work of Schlosser. Therefore, considering the feasibility of Knochel bases in DoMs and the potential application of fluorinated nitriles as building blocks, the first project comprised the regioselective metalation-functionalization of diverse fluorinated nitriles and their application in the synthesis of 4-aminoquinazolines. About 47 diverse functionalized nitriles (45-90%) with the exploration of new and scarcely investigated metalation sites were prepared by metalation with TMPMgCl.LiCl or (TMP)2Zn.2MgCl2·2LiCl. Besides, a difunctionalization strategy was possible and the building blocks were applied to construct relevant heterocycles. The 2,3-dihydroquinazolin-4(1H)-one (DHQ) is a privileged scaffold in a multitude of biologically active molecules including marketed pharmaceuticals and potential drug candidates. Glucose, as a renewable source, can be easily obtained from lignocellulosic biomass and applied in reduction processes under alkaline conditions. The only available method to directly access DHQs from 2-nitrobenzonitrile requires an excess of diboronic acid and copper as a catalyst in a water/methanol mixture. Thus, the second project envisioned the use of glucose as an eco-friendly reductant in an aqueous solution of potassium carbonate for the synthesis of DHQs from 2-nitrobenzonitrile in a one-pot fashion. A one-pot protocol based on nitrile hydration, nitro-reduction, imine formation, and cyclization with glucose in alkaline water was successfully established affording DHQs in yields 18-90%. No competition of the aldehyde from glucose with the externally added carbonyl compound was verified, and the synthesized DHQs in this work can be further converted to the corresponding quinazolinones finding even wider application in Medicinal Chemistry. Additionally, a study on the repositioning of the drug Tenofovir was performed.